Separação de leveduras do vinho fermentado através de dois hidrociclones comerciais de 10 milímetros - Pinto, André Arcelo (2014)
In plants of sugar industry, after the fermentation process to produce ethanol in the fermentation vats, the suspension of yeast and alcoholic solutions, called fermented wine, are forwarded to the centrifuges to make the separation of yeast that are reused in the process. This equipment, although efficient, requires large production costs, maintenance and energy, so new alternatives are being investigated to achieve this separation, one of which is the use of hydrocyclones. Due to these aspects, the aim of this study was to compare the separation of the yeast Saccharomyces cerevisiae present in fermented wine in two commercial hydrocyclones, Doxie® type A e AKW® type RWK 21, operating individually and in series, thus comparing their performances concerning the separation process. The independent variables selected for this study were: pressure feed for both hydrocyclones, the underflow pressure for Doxie hydrocyclone and the underflow diameter for AKW hydrocyclone. To evaluate the hydrocyclones performance a factorial design (3k) was carried out and the results were used to generate a mathematical models to describe the behavior of capacity, ratio of liquid, total efficiency of separation and reduced total efficiency. After the experiments and data processing, it was found that the hydrocyclone AKW showed superior performance hydrocyclone Doxie. To evaluate the performance of the two hydrocyclones, a factorial design was carried out (3k ) and the results were used to generate mathematical models in order to describe the behavior of the capacity ratio of liquid total efficiency of separation and reduced overall efficiency . It was also rated the performance of hydrocyclones using the serial configuration, using the operational and geometric configurations of equipment that showed the best results (capacity, total efficiency of separation, liquid ratio and reduced total efficiency). The decrease of cell viability was performed by cell staining assessed using methylene blue. With the use of the hydrocyclone Dachshund obtained results in capacity between 209 to 267.67 kg / h total efficiency from 16.72 to 63.87 % , total efficiency reduced from 5.86 to 39.39 % liquid ratios 11.54 to 40.39 % and a decline of 4.84% viability . Have the hydrocyclone AKW capacity was between values 216-311 kg / h , total efficiencies from 62.36 to 97.79 % , reduced total efficiencies from 23.08 to 88.27 % , net of reasons to 49,33 to 82.07 % and a decrease of cell viability of 6.98 % . With the use of hydrocyclones in series, there was a substantial increase in overall separation efficiency. Analysis and discussion of results , we found that increasing the supply pressure and decreasing the pressure underflow , considering the hydrocyclone Doxie , increased separation efficiency , the ability of equipment , but in return there was an increase in the ratio of net . The AKW hydrocyclone showed the highest values of total efficiency and separation using higher boost pressure and larger diameter of underflow.